Identification and validation of intergeneric hybrids between Saccharum officinarum and Erianthus rockii using molecular and cytogenetic tools - Gang Wang; Jianqiang Wang; Wei Zhang; Huanying Xu; Qinggan Liang; Yuanxia Qin; Qingdan Wu; Jiantao Wu; Cheng Fu; Feng Zhou; Yuxing An; Qinnan Wang; et al. (PLoS ONE, 2025)
Sugarcane (Saccharum spp.), a vital crop for sugar and bioenergy production, faces challenges in breeding due to its narrow genetic base and susceptibility to environmental stresses. To enhance genetic diversity, distant hybridization with wild relatives such as Erianthus rockii, known for its drought tolerance and strong ratooning ability, offers a promising strategy. However, identifying true intergeneric hybrids remains a critical challenge. This study identified true intergeneric hybrids from crosses between S. officinarum and E. rockii using tetra-primer ARMS-PCR and HRM curve analysis targeting SNPs in the nrDNA-ITS region, with genomic in situ hybridization (GISH) validating chromosome composition. The results confirmed 13 true hybrids among 16 progeny, showing a chromosome inheritance pattern of 40 chromosomes derived from S. officinarum and 15 from E. rockii. Hybrid plants, while exhibiting traits from both parents, displayed inferior yield and sugar content compared to the maternal parent, indicating the necessity for further backcrossing to improve agronomic performance. This study pioneers the application of ARMS-PCR and HRM in identifying E. rockii hybrids and underscores their potential in advancing sugarcane breeding by facilitating the introgression of beneficial traits from wild relatives.